Penyelenggaraan HOME BASED LEARNING pada jenjang SD Desa Kapedi - Izzah, Fajriyatul; Maulidi, Achmad (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
The focus of this research is on two things: How does home based learning run on SD lengths in Capedi Village? How does the relationship between school and parents in creating home based learning on the SD stretch in Capedi Village?. The method used in this research is a qualitative approach that is well known as naturalistic because its research is carried out in natural conditions. located in the captain's village, the data sources in this research are teachers, parents who have students, and children. while the data collection procedure uses interviews, observations, and documentation. checking the validity of the research data using the source triangle. This study shows that:The engraving is said to be boring because it's only using permanent learning methods or monotony. While parental and school relationships only occur between some parents and most parents do not have a special relationship to create home based learning in the SD range where pandemics. It's shown that it's important to evaluate PJJ-based learning such as parental retention and cooperation